A detailed analysis of mandibular fractures epidemiology, treatment and outcomes: A 5-year retrospective study, Gansu Province-China. Issue 3 (May 2018) - Abotaleb, Bassam M.; Al-Moraissi, Essam; Zhiqiang, Wang; Ping, Chen; Yongjie, Kang; Alkebsi, Khaled; Lan, Yang
Abstract: Purpose: The aim of the study is to comprehensively analyze the clinical epidemiology of the mandibular fracture including several factors which could affect the incidence, treatments, and outcomes of the mandibular fracture. Materials and methods: A retrospective study was conducted to include the patients with mandibular fractures in the department of maxillofacial surgery of the Lanzhou University second hospital from 2011 to 2015. The predictor variables were age, gender, ethnicity, medical health, habits, etiology, and treatment methods for mandibular fracture. The outcome variables were postoperative complications of MFs and corrective revision surgeries. T, Chi-square, Fisher's exact, and Spearmen statistical tests were used to analyze the data. Results: There were 342 patients with 571 fractures. Male/female ratio was 4.1:1 with the third decade accounted for (30.1%). Traffic accidents (43.6%) were the most common etiology followed by falls (31.6%). Symphysis/parasymphysis (26.4%) and condyle (24%) were the most common fracture sites. The complication rate was 18.4% with the infection (8.8%), and malocclusion (5.8%) were the most frequent complications. The rate of secondary operation was (5%). A high time interval to repairing was detected ( mean  = 11.04) without statistical significance between the rate of the overall complications and time interval to repairing ( P  = 0.957). Compromising factors significantly increase the rate of infection. There was no significant difference between the administration of antibiotics and the incidence of infection ( P  = 0.289). Conclusion: A well understanding of the epidemiology of mandibular fracture and variables' correlations is clinically important in advancing the prediction, diagnosis, treatment, and prevention of mandibular fractures in a particular population. Potential risk factors such as trauma severity, compromised medical health, and patient's behaviors were significantly affecting the resultant outcome. Open reduction and internal fixation of condyle fracture resulted in constant occlusal result than closed one. An antibiotic therapeutic effect against infection in mandibular fractures remains suspected. Time elapsing from injury to treatment had no influence on the overall complications.